IMPLEMENTASI PROGRAM KKN: SISTEM INFORMASI PENCATATAN DATA WARGA BERBASIS WEB DI KAMPUNG KERANJI GUGUH - Saputri, Cici; Septriyani, Rahma; Perdana, Rezky Ibnu Ferdi; Munthe, Marabona; Hamdani, Ripi; Salman, Salman; Ramadhan, Muhammad Rifki (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Community Service Program (KKN) is a form of community service carried out by students in a village using a cross-disciplinary approach at a specific time and location. Prototyping is an analysis and design technique that allows users to participate in determining needs and developing systems to meet those needs. The purpose of this application for the village is to help village-level institutions access information about the personal data of residents of Keranji Guguh Village. This KKN program uses a qualitative descriptive method that aims to explain phenomena occurring in the field. The development of the SIDaK Web for Keranji Guguh Village is a strategic project that requires a structured approach. It begins with careful planning involving all parties, followed by designing a good database and interface. The development stage uses appropriate technology (such as Laravel and Bootstrap) will affect the reliability of the system.